Moderation of Higher Education Curriculum in Religious Deradicalization in Indonesia - Ekawati, Ekawati; Suparta, M.; Sirin, Khaeron; Maftuhah, Maftuhah; Pifianti, Ade (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2019)
AbstractThis paper aims to know and analyze the forms of moderation of Islamic Higher Education curriculum. This moderate map of the curriculum is useful for policymaking in order to build an inclusive-multicultural awareness to minimize religious radicalism. This research is qualitative research with the historical approach. The method is used to examine the processes that take place in the life of the community under study. The results conclude that the forms of moderation of Islamic university curriculum in Indonesia are: first, integration and internalization of science. The Second, strengthening the theology of Rahmatanlil-'Alamin. Third, the deradicalization of religion through the strengthening of the local wisdom of Java. The Fourth, build an anti-radicalism curriculum. Fifth, the evaluation of multicultural-oriented learning. Sixth, Integral Muslim Personality Development Assistance Program (P3KMI). Seventh, Value Integration Plurality in the curriculum.Eighth, multicultural learning methods.AbstrakArtikel ini bertujuan untuk mengetahui dan menganalisis bentuk-bentuk moderasi kurikulum Pendidikan Tinggi Islam. Peta kurikulum yang moderat ini berguna untuk pembuatan kebijakan dalam rangka membangun kesadaran inklusif-multikultural untuk meminimalkan radikalisme agama. Penelitian ini adalah penelitian kualitatif dengan pendekatan historis. Metode ini digunakan untuk memeriksa proses yang terjadi dalam kehidupan masyarakat yang diteliti. Hasilnya menyimpulkan bahwa bentuk moderasi kurikulum universitas Islam di Indonesia adalah: pertama, integrasi dan internalisasi sains. Yang Kedua, memperkuat teologi Rahmatan lil-'Alamin. Ketiga, deradikalisasi agama melalui penguatan kearifan lokal Jawa. Keempat, bangun kurikulum anti-radikalisme. Kelima, evaluasi pembelajaran yang berorientasi multikultural. Keenam, Program Bantuan Pengembangan Kepribadian Muslim Integral (P3KMI). Ketujuh, Pluralitas Integrasi Nilai dalam kurikulum. Kedelapan, metode pembelajaran multikultural.How to Cite: Ekawati., Suparta, M., Sirin, K., Maftuhah, Pifianti, A. (2019). Moderation of Higher Education Curriculum in Religious Deradicalization in Indonesia. TARBIYA: Journal of Education in Muslim Society, 6(2), 169-178. doi:10.15408/tjems.v6i2. 14886.